The Motivation, Training, and Discipline on Employee Performance in Star-rated Hotels in Bogor City - Diyan Putranto; Marhanani Tri Astuti; Adi Sopyan; Anindita Gayatri; Barliani Dewi Setyawati; Albertus Banundoyo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research focuses on assessing the impact of motivation, training, and discipline on employee performance in star-rated hotels in Bogor City. Employee motivation, training, and discipline are identified as key factors influencing employee performance and, consequently, the success of the hotels. A quantitative research approach was adopted, and data from 220 respondents working in star-rated hotels was collected using a questionnaire. The results reveal that training and discipline significantly impact employee performance, while motivation alone does not have a significant effect. Based on the findings, recommendations are made to prioritize training, foster a disciplined work environment, and consider motivation strategies to improve employee performance and enhance the overall competitiveness of the hospitality industry in Bogor City. By implementing these recommendations, hotels can excel in service delivery and achieve higher levels of customer satisfaction and loyalty.